PENGARUH FREE CASH FLOW, PROFITABILITAS, STRUKTUR MODAL DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Radhwa Asmarani Nur Ibrahim; Muhammad Nuryatno Amin (EBID: Ekonomi Bisnis Digital, 2023)
The value of a company plays an important role in reflecting its condition based on stock prices. An increase in stock prices has a positive impact on shareholders' wealth, thereby maximizing their profits. This research is a quantitative study that utilizes the comparative causal research method. The variables examined include Free Cash Flow, Profitability, Capital Structure, and Dividend Policy as dependent variables, while Company Value serves as the independent variable. Secondary data from financial statements of companies listed on the Indonesia Stock Exchange for the period 2017-2021 were used in this study. The results of this research indicate that Free Cash Flow, Profitability, Capital Structure, and and significant effect on Corporate Value.